Human Resource Competencies, Digital Marketing, and Market Competition as Determinants of MSME Performance: The Mediating Role of Differentiation Strategy in Ungaran District - Kustiyono; Agung Wibowo; Abdul Aziz; Prattana Srisuk (Fundamental and Applied Management Journal, 2026)
MSMEs face increasing competitive pressures that require effective differentiation strategies, competent human resources, and the adoption of digital marketing practices to sustain business performance. This study examines the influence of human resource competencies, digital marketing, and market competition on MSME performance through the mediating role of differentiation strategy among MSMEs in Ungaran District, Central Java. A quantitative research design was employed involving 72 MSME owners and managers operating in Ungaran District, Central Java. Data were collected using structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that human resource competencies, digital marketing, and market competition contribute to the development of differentiation strategies among MSMEs. The structural model explains 59.4% of the variance in differentiation strategy and 13.5% of the variance in MSME performance. Differentiation strategy plays an important mediating role in linking organizational capabilities and market-oriented practices to MSME performance. The findings highlight the importance of integrating human resource competencies, digital marketing capabilities, and competitive market responses into effective differentiation strategies to enhance MSME performance and competitiveness.